Cobalt oxide supported multi wall carbon nanotube catalysts for hydrogen production via sodium borohydride hydrolysis. (3rd February 2021) - Narasimharao, Katabathini; Abu-Zied, Bahaa M.; Alfaifi, Sulaiman Yahya
Abstract: Cobalt oxide supported multi-wall carbon nanotubes (Co/MWCNTs) catalysts with different cobalt oxide loadings were synthesized by simple impregnation method. The synthesized Co/MWCNTs materials were used as catalysts for hydrolysis of sodium borohydride (NaBH4 ), an effective route to produce clean hydrogen. The effect of some parameters such as Co loading, reaction temperature and reaction time were investigated on the performance of catalysts in hydrolysis of NaBH4 . The hydrogen generation rate was found to be 409 mLg −1 min −1 at 35  ° C for Co/MWCNTs-20 catalyst in NaBH4 hydrolysis, while it is 28 mLg −1 min −1 for bulk MWCNTs support. The physico-chemical characteristics such as crystalline phase, morphology, particle size, reducibility, surface and textural properties of the catalysts were studied by using powder XRD, FE-SEM, TEM, N2 -physorption, XPS and H2 -TPR techniques. The reduction temperature of cobalt oxide species was shifted to lower temperatures after impregnation of nanosized Co oxides on the MWCNTs support. It was also observed that presence of more number of surface Co 2+ species in Co/MWCNTs-20 catalyst is responsible for superior activity in catalytic hydrolysis of NaBH4 . The obtained results also suggested that Co/MWCNTs catalysts can be reused for five cycles with a slight loss of activity. Graphical abstract: Image 1 Highlights: Synthesis of cobalt oxide supported multi-wall carbon nanotubes catalysts. Efficient catalytic performance in hydrolysis of NaBH4 . Hydrogen generation rate 409 mLg −1 min −1 at 35  ° C without using alkali. More number of surface Co 2+ species in samples are responsible for high activity. Co/MWCNTs-20 catalyst is a superior catalyst for hydrolysis of NaBH4 .